Pudelek? Polityka? Przybora? Dobór tekstów do analizy na zajęciach językoznawczych - Piętkowa, Romualda (Forum Lingwistyczne, 2014)
Pudelek? Polityka? Przybora? Selecting texts for analysis on linguistics classes The article describes three spheres of culture which can be used as sources of texts for linguistics classes, evoked by the nicknames mentioned in the title: Pudelek.pl (a gossip website) as a source of mass culture texts, Polityka (a widely-read opinion weekly) as an example of the political discourse, and finally Jeremi Przybora (a perfectionist lord of the Polish language) as an example of the highbrow culture texts. The article results from author’s own teaching experience. She introduces vocabulary of the public discourse, distinguishing between the “flagship” words, the winged words, and the words that changed their due to the influence of political correctness (i.e. words which were “turned inside out”). Particularly important here seem to be the winged words which, characterized by their condensed form, are able to built both cultural continuity and group identity. Therefore, amongst the selected texts are also those by/about the persons related to university. Key words: winged words, political correctness, mass culture, linguistics classes